Bias, bullshit and lies: audience perspectives on low trust in the media - Newman, N; Fletcher, R (Reuters Institute for the Study of Journalism, 2017)
Even in a world where people increasingly get news from social media, the professional news media is still seen as largely to blame for low trust according to a new report from the Reuters Institute for the Study of Journalism, which examines the underlying reasons for trust and distrust in the news media (and in social media) across nine countries. Bias, spin and hidden agendas come across as the main reasons for lack of trust in the news media along with a perceived decline in journalistic standards driven by greater competition and some online business models. These concerns are strongest with the young and with those on low incomes. Trust in the news that people find in social media is lower still, but similar trends are at play - bias, agendas and low quality information. The report argues that this is largely a function of a model that allows anybody to publish without checks, and algorithms that sometimes favour extreme or contentious content. The study is based on analysing thousands of open-ended responses from the 2017 Reuters Institute Digital News Report, where respondents were asked to give their reasons for low trust in their own words, using open-ended text fields. By coding and analysing responses, the report categorises the specific issues that are driving public concern across countries as well as those that build trust such as journalistic processes, strong brands and quality journalism delivered over time.